The Icon as a Medium to Construct a Saint’s Image. The Earliest Icons of Saint Nil Stolbenskii - Thyrêt, Isolde (IKON, 2016)
Abstract The earliest icons of Nil Stolbenskii from the Lake Seliger region in western Russia played an important role in the development of the saint’s cult after the composition of his vita and liturgy at the turn of the 17th century. Taking their cue from Nil’s liturgy, the creators of Nil’s iconography modeled the image of the holy man after the White Sea saint Savvatii of Solovki, whose veneration, together with that of his fellow saint Zosima, became popular in 16th century Russia. Like the early images of the Solovetskii saints, the first non-extant icons of Nil depict their subject as an island saint. The earliest extant icons of the saint, which date from after 1635, express Nil’s spiritual pursuit, his austere asceticism and his pursuit of union with God (theosis), described in his vita, by depicting the saint standing in the wilderness of Stolbnoe Island and communicating with Christ behind a band of clouds. In order to proclaim the lasting spiritual impact of the saint, the designers of these icons used a new iconographic tradition in Muscovy to portray Nil as a monastic founder. By fusing this concept with the recently created composition The Monastery of Zosima and Savvatii, Nil’s iconographers found an effective means to emphasize the Seliger’s saint’s continuing miracle-working power. The dual depiction of Nil as an ascetic/God-seeker in the foreground and as a relic inside the Nilov Hermitage in the center of Nil’s 17th century icons made a convincing case for the saint’s permanent veneration.